Stygobiotic faunal elements in spring assemblages of West Transcaucasia - Dmitriy M. Palatov (Cherepovets State University, 2019)
Macroinvertebrates of stygobiotic origin contributing to benthic assemblages in springs of the two regions of West Transcaucasia were investigated. The regions concerned, basins of the KhostaKudeps ta Rivers (Krasnodarskiy krai) and Myussera Upland (Abkhazia), are wellstudied and drastically different in a number of features. Frequency of occurrence, abundance and the position of stygobiotic species in the structure of crenal assemblages are given. Stygobionts dominated in 50% of cases, more often in helocrenes with variable runoff than in rheocrenes stably connected with watercourses. Stygo and crenobiotic primary aquatic invertebrates (crustaceans and mollusks) demonstrate pronounced local endemism at the species level. Under certain circumstances spring assemblages can be considered as island ones.